PELATIHAN PENERAPAN MANUAL PROSEDUR PERAWATAN DAN PERBAIKAN MESIN PEMBUAT PELLET BAGI KELOMPOK TANI ASA MINA MULIA MIJEN SEMARANG - Ireng Sigit Atmanto; Sri Utami Handayani; Seno Darmanto; Didik Ariwibowo (Jurnal Pengabdian Vokasi, 2021)
Catfish is one source of animal protein that is highly nutritious and popular, so it has a bright prospect of cultivating by the community. In catfish farming, the main factor determining fish growth and production costs is fish feed.  It is easier to control the nutrient intake and reduce production costs if catfish farmers can make fish feed independently. Ownership of a fish pellet machine is advantageous for the fish farmer group because the machines can be used interchangeably. Members of the farmer group need to understand how to operate, maintain and repair fish pellet machines so that the machine has a longer service life. This community service activity provides maintenance and repair training for fish pellet machines for the farmer group Asa Mina Mulia Mijen, Semarang.